Factors associated with changes in self-reported health status in infliximab-treated inflammatory bowel disease patients: results from a case management survey. (July 2015) - Kanters, Steve; Thorlund, Kristian; Perampaladas, Kuhan; Dyrda, Peter; Williamson, Martin; Jones, Jennifer
Abstract : Background: Canadian inflammatory bowel disease patients treated with infliximab are predominantly managed through a nationwide case management system, named BioAdvance ® . Methods: A web-based survey was provided to patients currently receiving infliximab therapy within BioAdvance ® . Patients were categorized according to health trajectories: decliners, non-changers, moderate increasers and strong increasers. Factors associated with health trajectories were identified using multivariable multinomial logistic regression. Results: 918 of 1160 respondents were inflammatory bowel disease patients reporting health status. Strong increasers were more likely to use educational tools than non-changers (adjusted odds ratio [aOR]: 1.65; 95% CI: 1.03–2.64), to be treated for ulcerative colitis (aOR: 2.05; 95% CI: 1.16–3.64) and to perceive case management as important (aOR: 2.52; 95% CI: 1.56–4.09). Younger (aOR: 0.72; 95% CI: 0.63–0.83) and French-speaking (aOR: 0.34; 95% CI: 0.18–0.63) patients were less likely to miss workdays. Patients were more likely to have missed workdays prior to joining the case management program. Conclusions: Inflammatory bowel disease patients receiving infliximab within the nationwide case management system report a positive impact on health status and absenteeism.